Marketing strategies of Generation Z influencers in Mexico - Tornel Lagunes, Daniel Antonio; Cornelio Marí, Elia Margarita; Hernández Romero, Gladys (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To analyze the digital marketing strategies used by Generation Z influencers in Mexico, focusing on celebrities such as Domelipa, Kim Loaiza, and Ralf Morales, who were selected due to their outstanding popularity and ability to influence the purchasing decisions of their followers.MATERIAL AND METHOD: A detailed study through a qualitative case study analysis of the content generated by these influencers was conducted. Tactics such as gamification, user-generated content (UGC), and brand collaborations were examined to evaluate their effectiveness in promoting and engaging Generation Z.RESULTS: The results reveal a significant increase in conversion rates and user engagement in campaigns that incorporate these strategies, highlighting authenticity and emotional connection as key factors.CONCLUSIONS: This work provides an original perspective by focusing on the Mexican context, offering a comprehensive analysis of how national influencers use innovative techniques to connect with their audiences. It also highlights the importance of adapting marketing strategies to the specific characteristics of this generation, emphasizing the importance of authenticity in digital interaction.
Keywords: digital marketing strategies; social media; gamification; user-generated content; case study.